The Modelling of Groundwater Table Management for Canal Blocking Scenarios In Sub Peatland Hydrological Unit - Ivan Aliyatul Humam; Abdul Chalid; Bagus Prasetyo (Publisher Cv. Inara, 2020)
Drainage in peatland caused reducing water storage and subsidence. Groundwaterlevel fluctuations are a major role in the water balance that occurs in peatlands. Theresearch was conducted in a specific area of agricultural peatland. The location inSub-Peatland Hydrological Unit (Sub- PHU) 5 and 6 Kahayan Sebangau, CentralKalimantan Province, Indonesia. Modeling for groundwater table was applied usingFreewat / Modflow software with input rainfall probability 80% (R80), infiltration,and evapotranspiration data analysis. Groundwater table should not be less thanminus 0.4 meters based on the Indonesian Ministry of Environment and Forestry(Menlhk). The deficit means the groundwater level below -0.4 m and surplus uponthe criteria. Land modeling is simulated with an area of 300 x 1000 meters. Thecalibration in the model was found conductivity values, 50 m / day or 5.78 x 10-4 m /s with the best value with the largest NSE and Correlation. The modeling showedthat the deficit occurred in seven months. The groundwater management is how tokeep the water level upon -0.4 m with the planning of canal blocking height. Thescenarios are 0.2 m. 0.3 m, 0.4m, and 0.5 m upon the base flow of the canal. Thebest scenario was chosen 0.5m according to the simulation which has the waterlevel upon -0.4 m.